Imaging and identification of endogenous peptides from rat pituitary embedded in egg yolk. (15th January 2015) - Sosnowski, Piotr; Zera, Tymoteusz; Wilenska, Beata; Szczepanska‐Sadowska, Ewa; Misicka, Aleksandra
Abstract : Rationale: Mass spectrometry imaging (MSI) can provide accurate data containing the spatial distribution of endogenous peptides in tissue sections without previous treatment. One of the key issues in analyzing small samples is establishing a proper technique for mounting and manipulating collected tissue in order to avoid contamination of the sample with optimal cutting temperature (OCT) resin. Methods: We present a method for embedding rat pituitary tissue in a frozen egg yolk block, which enables its further imaging in experiments on a matrix‐assisted laser desorption/ionization (MALDI) mass spectrometer with time‐of‐flight (TOF) analyzer. Embedding the sample in the egg yolk prevents contamination from the OCT resin, which decreases MALDI signal quality. Results: In the present study we detected numerous m/z peaks related to endogenous peptides. We identified fifteen peptides and their post‐translational modifications by tandem mass spectrometry (MS/MS) directly on tissue sections of the hypophysis posterior and intermediate lobes; among these peptides were vasopressin, oxytocin, copeptin, melanocyte‐stimulating hormones and beta‐endorphin. We also showed that egg yolk itself does not affect localization of peptides in the pituitary. Conclusions: Egg yolk embedding enables preparation of tissue sections from small tissue fragments to organs such as the pituitary gland, which is suitable for localization and identification of endogenous peptides by the MALDI‐MSI and MALDI‐MS/MS techniques. Copyright © 2015 John Wiley & Sons, Ltd.